Comparison Of Analgesic Effect Of Subcutaneous Bupivacaine Infiltration And Intravenous Diclofenac Vs. Intravenous Diclofenac Alone In Inguinal Hernioplasty: A Retrospective, Single Centre Study In Gaza - S Alijla, Said S (2023)
Postoperative pain is a significant problem encountered by patients after a surgical intervention, and there is a crucial need for effective postoperative pain control. Studies showed that multimodal analgesia and wound infiltration are effective ways to reduce this pain and have a substantial role in the reduction of postoperative medications requirement. This study aimed to evaluate the effect of subcutaneous infiltration of bupivacaine hydrochloride and intravenous diclofenac as postoperative pain relief in adults undergoing inguinal hernia repair. A single-centre retrospective case-control study included 104 patients aged 18-65 undergoing unilateral inguinal hernia repair at the selected hospital. The patients were in two groups of 52 each. Group A received 75 mg dose of IV diclofenac plus a subcutaneous injection of 10 mL of bupivacaine hydrochloride (HCl) 0.5% while Group B only received the IV diclofenac alone. The postoperative pain was assessed at one, two, three, six, and 12 hrs after the operation using the visual analog scale (VAS), which exhibited a range of pain from zero (no pain) to 10 (extreme pain). Of a total of 104 patients, 92% of patients were male. The mean age was 36 ± 11 years, and the mean body mass index (BMI) was 22 ± 3 kg/m2. American Society of Anesthesiologists physical class I was statistically insignificant between both groups (90.4% versus 84.6%).